2020
DOI: 10.1002/cmdc.202000865
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Fragments Binding to the PDZ1‐2 Domain of PSD‐95

Abstract: Inhibition of PSD‐95 has emerged as a promising strategy for the treatment of ischemic stroke, as shown with peptide‐based compounds that target the PDZ domains of PSD‐95. In contrast, developing potent and drug‐like small molecules against the PSD‐95 PDZ domains has so far been unsuccessful. Here, we explore the druggability of the PSD‐95 PDZ1‐2 domain and use fragment screening to investigate if this protein is prone to binding small molecules. We screened 2500 fragments by fluorescence polarization (FP) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Interestingly, it has been a trend for researchers to choose FP as the only or involved screening assay combined with other classical screening assays to identify hits from a large fragment library in recent years. For example, Zang et al employed FP during the first screening of 2500 fragments for small molecules binding to the PDZ1-2 domain of PSD-95 in 2021 . Sixty-five primary hits with 2.5% hit rate reversed the previous thought that PDZ domains are nondruggable.…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it has been a trend for researchers to choose FP as the only or involved screening assay combined with other classical screening assays to identify hits from a large fragment library in recent years. For example, Zang et al employed FP during the first screening of 2500 fragments for small molecules binding to the PDZ1-2 domain of PSD-95 in 2021 . Sixty-five primary hits with 2.5% hit rate reversed the previous thought that PDZ domains are nondruggable.…”
Section: Perspectivementioning
confidence: 99%
“…For example, Zang et al employed FP during the first screening of 2500 fragments for small molecules binding to the PDZ1-2 domain of PSD-95 in 2021. 129 Sixty-five primary hits with 2.5% hit rate reversed the previous thought that PDZ domains are nondruggable. This result showed that FP could be developed into a robust, potential, and promising fragment screening method.…”
Section: ■ Perspectivementioning
confidence: 99%